Pelatihan Penulisan Penelitian Tindakan Kelas pada Guru di Lingkungan Muhammadiyah Boarding School Ki Bagus Hadikusumo - M Koesmawan; Elliya Sestri; Isnan Hari Mardika (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2019)
Writing scientific papers is a very important activity for a professional teacher. This activity not only needs to be done in order to obtain credit figures for promotion or for the purposes of certification through portfolios, but moreover, it needs to be done in order to improve the quality of classroom management, quality of service to students, and also increase the professionalism of the teacher himself. The results of the overall community service activity can be seen based on the following components. First, the target of the training participants or target audience is 36 Muhammadiyah Boarding Schools (MBS) Ki Bagus Hadikusumo. In the implementation of this activity, it was attended by 22 teachers because there were several teachers who had activities outside of school. Thus the target number of training participants is 61.1% or can be considered quite good. Secondly, the achievement of training objectives can be judged to be poor. Within a period of two weeks as many as 9 teachers (40.9%) had tried to prepare a proposal